A Comparison of the Quality of Meat from Female and Male Californian and Flemish Giant Gray Rabbits - Tomasz Daszkiewicz; Andrzej Gugołek (Animals, 2020)
This study aimed to compare the quality of meat (Longissimus thoracis et lumborum—LTL, hind legs—HL) from female and male Californian (CAL) and Flemish Giant Gray (FG) rabbits. The animals were kept outdoor, in a roofed pavilion, in wire mesh cages with a slatted floor and were fed ad libitum a complete pelleted diet. All rabbits were slaughtered at 91 days of age. The meat of CAL rabbits had a higher content of dry matter (p < 0.001), protein (p < 0.001) and unsaturated fatty acids (p = 0.002), higher pH (p < 0.001), and higher taste desirability (p = 0.021) and tenderness (p = 0.046). CAL rabbit meat had also a lower (p < 0.001) water to protein (W/P) ratio, lower (p < 0.001) shear force values, and lower (p = 0.042) taste intensity. The meat of FG rabbits was characterized by lower (p < 0.001) water-holding capacity (WHC). The LTL muscle had a higher content of dry matter (p = 0.003) and protein (p < 0.001), higher L* (lightness) (p = 0.011), b* (yellowness) (p < 0.001), and C* (chroma) (p = 0.010) values, and lower (p = 0.015) WHC. Hind leg muscles had higher (p < 0.001) fat content, a higher (p < 0.001) W/P ratio, and pH (p < 0.001). Sex had no effect (p > 0.05) on the analyzed meat quality attributes, excluding vitamin A content which was higher (p = 0.041) in females. In conclusion, the meat of CAL rabbits slaughtered at 91 days of age can be more mature than the meat of FG rabbits slaughtered at the same age. Furthermore, quality of meat from rabbits of both breeds depends on the anatomical origin of muscles. Further research is needed to identify the possible reasons for the higher vitamin A content of meat from female rabbits which did not differ from the meat of males in terms of other characteristics.